2014
DOI: 10.1371/journal.pone.0098542
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in the Abundance and Composition of Biofilm Communities Colonizing Drinking Water Distribution Pipes

Abstract: Pipes that transport drinking water through municipal drinking water distribution systems (DWDS) are challenging habitats for microorganisms. Distribution networks are dark, oligotrophic and contain disinfectants; yet microbes frequently form biofilms attached to interior surfaces of DWDS pipes. Relatively little is known about the species composition and ecology of these biofilms due to challenges associated with sample acquisition from actual DWDS. We report the analysis of biofilms from five pipe samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 57 publications
7
56
1
Order By: Relevance
“…Mycobacterium occurrence in IW was not surprising as it was recently reported by Kelly and collaborators to be among the dominant taxa of biofilms in drinking water distribution pipes with concentrations up to 14% (Holinger et al, 2014;Kelly et al, 2014), in accordance with a number of parameters such as nitrate, ammonium, total chlorine and monochloramine concentrations. In contrast, the high relative abundance of Propionibacterium highlighted in IW was not expected since the bacteria related to this genus are usually found on the skin (Scharschmidt and Fischbach, 2013).…”
Section: Discussionsupporting
confidence: 56%
“…Mycobacterium occurrence in IW was not surprising as it was recently reported by Kelly and collaborators to be among the dominant taxa of biofilms in drinking water distribution pipes with concentrations up to 14% (Holinger et al, 2014;Kelly et al, 2014), in accordance with a number of parameters such as nitrate, ammonium, total chlorine and monochloramine concentrations. In contrast, the high relative abundance of Propionibacterium highlighted in IW was not expected since the bacteria related to this genus are usually found on the skin (Scharschmidt and Fischbach, 2013).…”
Section: Discussionsupporting
confidence: 56%
“…including A. lwoffii are known not just as opportunistic pathogens but also ubiquitous habitant in biofilm in water distribution systems. (Scott and Pepper, 2010;Vaz-Moreira et al, 2013;Kelly et al, 2014). This result suggests that inflammatory potency can increase with the regrowth of Acinetobacter sp.…”
Section: Comparison Of Inflammatory Responses Caused By the Purified mentioning
confidence: 80%
“…At the family level, one taxon that showed significantly higher proportional abundances in Vietnamese pit latrines compared with those in Tanzania was the Xanthomonadaceae, typically characterized as environmental organisms which are found in soil and water, as well as plant tissues (Arrieta-Ortiz et al, 2013;Hui et al, 2014;Kelly et al, 2014). Recent studies have shown degradation properties for organisms from this family (Cea et al, 2010;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%